Tissue‐specific expression of insulin receptor isoforms in obesity/type 2 diabetes mouse models - Moruzzi, Noah (J Cell Mol Med, 2021)
The two insulin receptor (IR) isoforms IR‐A and IR‐B are responsible for the pleiotropic actions of insulin and insulin‐like growth factors. Consequently, changes in IR isoform expression and in the bioavailability of their ligands will impact on IR‐mediated functions. Although alteration of IR isoform expression has been linked to insulin resistance, knowledge of IR isoform expression and mechanisms underlying tissue/cell‐type‐specific changes in metabolic disease are lacking. Using mouse models of obesity/diabetes and measuring the mRNA of the IR isoforms and mRNA/protein levels of total IR, we provide a data set of IR isoform expression pattern that documents changes in a tissue‐dependent manner. Combining tissue fractionation and a new in situ mRNA hybridization technology to visualize the IR isoforms at cellular resolution, we explored the mechanism underlying the change in IR isoform expression in perigonadal adipose tissue, which is mainly caused by tissue remodelling, rather than by a shift in IR alternative splicing in a particular cell type, e.g. adipocytes.